Implementation of School Administration Management in SMK Negeri 1 Palembang - Maisyar Darmayanti; Yasir Arafat; Meilia Rosani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study aims to determine the management of school administration at SMK Negeri 1 Palembang. This research uses a qualitative approach to descriptive analysis methods. Data collection techniques in the form of interviews, observation, documentation. The location of this research was conducted at SMK Negeri 1 Palembang. The results of the study, (a) teacher administration by school administration staff at SMK Negeri 1 Palembang includes the activities of administering teacher completeness and the quality of implementing teacher administration at SMK Negeri 1 Palembang is carried out well, (b) the quality of implementing student administration at SMK Negeri 1 Palembang in general can be classified into good criteria. (c) the implementation of personnel administration at SMK Negeri 1 Palembang has several weaknesses, namely in terms of planning for the needs of teaching and educational staff which are usually carried out by the teachers themselves and in the process of appointment, transfer and promotion which is still not optimal.